Automatisk identifiering av outnyttjade byggrätter - En studie om digital detaljplaneinformation och utveckling av ett digitalt sökverktyg - Hilding,Isabelle (Examensarbete i geografisk informationsteknik, 2025)
Being able to identify unused development rights is of interest for both private and public actors. For private actors, this need arises, for example, in new construction projects, and for public actors, another need may instead be to have better control over their planning readiness. Searching and calculating development rights manually can be time consuming and for private actors this can also lead to missed opportunities. A digital tool can therefore be seen as a solution for combining multiple data sets, identifying unused development rights and presenting this information to the end user. This study aims to investigate the possibilities of developing a digital search tool for automatic identification of unused development rights, using today’s available data sets. The report begins with a theoretical background to describe central concepts. Four studies are then carried out, the first of which is based on a manual identification of unused building rights, where ten densification opportunities within the selected study area are identified. In the second study, a digital search tool for automatically identifying unused development rights, ByggrättSök, is developed. The Python programming language is used to consume data from Nationella Geodataplattformen (NGP) by applying APIs intended for consumers. The Python library Streamlit is used in the development of an interactive web application. In the third study, the developed search tool is evaluated by examining how well it performs compared to manual identification of unused development rights. Furthermore, a control check is made of the tool’s calculation of building rights based on how well it performs in relation to manual calculations. The data sets used by the tool are examined, as well as the tool’s filtering options, to see how these can have an impact on the result. In the final study, eight aspects are selected, which are considered to have an impact on whether the identified unused development rights can be realizable. The tool’s improvement potential is identified by studying its ability to take these aspects into account. In conclusion, the results demonstrate that a digital search tool for automatic identification of unused development rights can be developed. However, the tool does not currently have the ability to automatically generate search results for only realizable unused development rights. For the tool to be able to consider some of these aspects, filtering options can be implemented with relatively simple means by applying information from already existing data sets. In other cases, more complex analyses are required to handle qualitative variables.
Keywords: Digital detaljplaneinformation; Nationella Geodataplattformen (NGP); Outnyttjad byggrätt